Ответы 1

  • (8х + 10) * (3 - х) = (11 - 2х) * (4х + 5) - 5;

    24х - 8х^2 + 30 - 10х = 44х + 55 - 8х^2 - 10х - 5;

    - 8х^2 + 8х^2 + 14х - 34х = 50 - 30;

    - 20х = 20;

    - х = 20 : 20;

    - х = 1;

    - х * (- 1) = 1 * (- 1);

    х = - 1;

    (8 * (- 1) + 10) * (3 - (- 1)) = (11 - 2 * (- 1)) * (4 * (- 1) + 5) - 5;

    (- 8 + 10) * 4 = (11 + 2) * (- 4 + 5) - 5;

    2 * 4 = 13 * 1 - 5;

    8 = 8.

    • Автор:

      gordo3fbp
    • 3 года назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years